On some characteristics and related properties for OWF and RIM quantifier. Issue 6 (14th March 2018) - Wang, Jian; Kalina, Martin; Mesiar, Radko; Jin, Le Sheng
Abstract: Regular Increasing Monotone (RIM) quantifier and Ordered Weighted Function are important counterparts of discrete ordered weighted averaging operators. Some important characteristics such as entropy, Moment, and Step/Hurwicz degree have already been proposed and studied by several researchers. The main propose of this paper is to put the concepts of entropy, Moment, and Step/Hurwicz degree for RIM quantifier into a continuous environment. Some well‐defined representative families of RIM quantifiers are also presented. The metric spaces of RIM quantifiers are discussed.